Slow Debt, Deep Recessions - Joachim Jungherr; Immo Schott (American Economic Journal: Macroeconomics, 2022)
Business credit lags GDP growth by about one year. This contributes to high leverage during recessions and slow deleveraging. We show that a model in which firms use risky long-term debt replicates this slow adjustment of firm debt. In the model, slow-moving debt has important effects for real activity. High levels of firm debt issued during expansions are only gradually reduced during recessions. This generates an adverse feedback loop between high default rates and low investment and thereby amplifies the downturn. Sluggish deleveraging slows down the recovery.
Keywords: E23; E32; E44; G31; G32; 330